Magnitude of benefit of the addition of poly ADP-ribose polymerase (PARP) inhibitors to therapy for malignant tumor: A meta-analysis. (March 2020) - Gu, Lihu; Du, Nannan; Jin, Qiong; Li, Shengnan; Xie, Laidi; Mo, Jiahang; Shen, Zefeng; Mao, Danyi; Ji, Jia; Khadaroo, Parikshit Asutosh; Chen, Bangsheng
Highlights: PARP inhibitors can significantly improve the long-term survival rate of tumor patients. PARP inhibitors are more suitable for ovarian cancer patients with BRCA1/2 mutations. Although PARP inhibitors may increase the risk of adverse reactions, it is generally safe and controllable. Abstract: Background: The purpose of this study was to analyze the efficacy of PARP inhibitor on solid tumors. Methods: For this study, the following databases were searched for articles published from its inception until July 2019: PubMed, Web of Science, EBSCO, and Cochrane library, of which the main conclusion was the overall survival (OS) and progression-free survival (PFS). Results: We conducted a meta-analysis and the results showed that PARP inhibitor increased the patients' PFS (HR: 0.51, p < 0.001), PFS with BRCA1/2 mutations (HR: 0.32, p < 0.001), OS (HR: 0.74, p < 0.001), OS with BRCA1/2 mutations (HR: 0.78, p = 0.03), complete response (CR) (RR: 1.89, p = 0.10), partial response (PR) (RR: 1.34, p = 0.01), overall response rate (ORR) (RR: 1.42, p = 0.001) respectively. The main adverse events (AEs) observed were decreased appetite. Conclusions: PARP inhibitors may prolong survival. PARP inhibitors were more favorable for BRCA1/2 mutations in ovarian cancer patients. Additionally, the overall safety factor was controllable.